Peran Inovasi Berkelanjutan Dalam Transformasi Ekonomi Kepulauan Yang Inklusif - Gema Bangsawan (Jurnal Archipelago, 2025)
Island economies face complex economic barriers and environmental threats. To address these issues while prioritizing sustainability, innovative solutions are required. This research aims to analyze the role of sustainable innovation in inclusive and sustainable island economic transformation. By identifying creative solutions from existing opportunities and developing sustainable solutions to infrastructure limitations, the paper explores how innovation can overcome these challenges. Sustainable innovation can empower vulnerable groups, enhance productivity, reduce environmental impacts, and promote climate resilience. For instance, developing environmentally friendly and efficient maritime transportation technologies can improve connectivity and reduce environmental impacts. Additionally, innovative agricultural technologies can enhance productivity and food security in remote islands.Innovation can also foster inclusivity by creating new economic opportunities for vulnerable groups. This can be achieved through the application of appropriate technologies in agriculture and fisheries, including self-reliant production to increase product value, skills training, and participatory social infrastructure development. Furthermore, approaches to increase the participation of vulnerable groups in local economic supply chains can strengthen social and economic inclusion. To achieve sustainability, developing renewable energy technologies can help reduce reliance on fossil fuels and carbon emissions in island regions. Additionally, infrastructure sharing, training for home-based creative industries, processing of unique island products, and the utilization of alternative mobile air transportation (drones) can provide innovative solutions.By implementing these innovations, positive impacts are expected, including economic sector diversification, inclusive policy implementation, and improved quality of life for island communities. Through an integrated sustainable innovation approach, innovation can be a key driver of inclusive economic growth in island regions.